Fishermen’s Legal Awareness of The Use of Fish Bombes In Bombana District Water Area (Study At Direktorat Pol.Air Sultra) - Bariun, La Ode; Arifin, Djohar; Munawir, La Ode; Basoddin, Basoddin; Napitupulu, Parulian; Sunariyanto, Sunariyanto (International Journal of Management and Education in Human Development, 2023)
The Republic of Indonesia is one of the largest archipelagic countries with a sea area of 3,257,483 km2, not including the waters of the Exclusive Economic Zone (EEZ) with 13,667 islands. Apart from that, Indonesia is rich in culture, language, and abundant natural resources. As stated in the 1945 Constitution, "The Unitary State of the Republic of Indonesia is an archipelagic country characterized by an archipelago with territories whose boundaries and rights are determined by law."The sea and coastal areas surrounding Indonesia contain enormous and diverse economic potential, so Indonesia is known as the largest archipelagic country with the greatest marine biodiversity. Biological resources found in Indonesian seas include fish, mangroves, coral reefs, and seagrass beds, and non-biological resources in the form of petroleum, natural gas, and mining. This research is planned for two months and is planned to be carried out with the completion of the Proposal Seminar in March after which it will be continued with research which will be planned in March and April 2023 in Bombana Regency, Southeast Sulawesi Province. Based on the results of the research analysis and discussion, the following conclusions can be drawn: 1). The level of legal awareness of fishermen in Lora Village, Mata Oleo District, Bombana Regency is classified as low. 2). Factors that influence the level of legal awareness of fishermen in Taspuhai Village, Central Rumbia District, Bombana Regency, namely: a. Internal factors (1) Fisherman's legal knowledge is high, (2) Fisherman's understanding of the law is low, (3) Attitude towards the law is low, (4) Fishermen's legal behavior patterns are low. b. External Factors (1) Education, (2) Economic Conditions, (3) Lack of cooperation between Fishermen and the Government. 3). Efforts made to increase the legal awareness of fishermen in Lora Village, Mataoleo District, Bombana Regency, namely conducting socialization of the law, having COREMAP placed in each village, and providing alternative aid funds.